Laura Owens - Owens, Laura 1970- (Skira Rizzoli, 2015)
"This volume - modeled after the seminal book on Pablo Picasso's sketchbooks 'Je Suis Le Cahier: The Sketchbooks of Picasso' published in 1986 - brings together a range of critical and creative voices to consider her practice in depth."
Keywords: Owens, Laura / Criticism and interpretation; Owens, Laura -- 1970-; Geschichte 2008-2011; Geschichte 1994-2006; Painting, American / 21st century; Mixed media (Art) / United States / 21st century; Animals in art / 21st century; Painting, Abstract / 21st cnetury; Collage; Malerei; USA; Bildband